Docetaxel Loaded Folate Targeted Nanoemulsions for Improved Efficacy Against Ovarian Cancers [30P]. (May 2016) - Patel, Niravkumar; Piroyan, Aleksandr; Davis, Barbara; Coleman, Timothy
Abstract : INTRODUCTION: Ovarian cancer ranks fifth in cancer related deaths in women. It has high mortality rate and is associated with high recurrence rate of 60 to 80%. It is well established that recurrent tumors are more likely to exhibit multidrug resistance phenomenon leading to unfavorable response from second and third line chemotherapy. Nanoemulsions are emerging as an attractive drug delivery system to overcome many of the challenges presented by such tumors. We have developed folate targeted gadolinium annotated nanoemulsion system loaded with docetaxel. These nanoemulsions have been developed as theranostic agents as gadolinium will enable physician to acquire real time data on distribution of nanoemulsions. METHODS: Nanoemulsions were synthesized using high shear micro fluidization method and characterized for size, zeta and loading efficiency. Folate density on these nanoemulsions was optimized using flow cytometry. In vitro cytotoxicity data were obtained using MTT assay. In a Nu/Nu mouse SKOV-3IP orthotropic model, MRI was used to demonstrate diagnostic properties of these nanoemulsions to quantitate tumor nodule development in a longitudinal manner. RESULTS: Data indicate that 1200 molecule/particle of folate is ideal for achieving improved cell uptake and also capable of competing of free folate. In vitro data showed improved potency of docetaxel nanoemulsions and reversal of multidrug resistance phenomenon. In vivo, gadolinium annotated nanoemulsions were capable of detecting tumor nodules on longitudinal manner. CONCLUSION: Improved potency against resistant cells and ability to detect tumors on longitudinal manner makes these nanoemulsions ideal candidate for further clinical development as theranostic agent.